The reanalysis in the spanish diachrony - Casas Navarro, Raymundo (2012)
In this article, we work with the category of reanalysis to shed light on a series of changes in the history of the Spanish language, and thereby to overcome the mere description level with the purpose of achieving the core goal of Science: theoretical explanation. In order to accomplish our mission, we base our work on the framework drawn up by Langacker (1977). The theoretical Langackerian framework sets a clear concept of reanalysis and produces a clear distinction of their types, causes, and effects. Firstly, we will make a concise presentation of Langacker’s notions, above all, those regarding to the types of reanalysis. Then we will focus on some diachronic processes of the Spanish language that can be clarified in terms of the Langackerian category. Finally, we will expose some corollaries resulting from this framework to underpin a cognitiveview of linguistic change.